2019
DOI: 10.1039/c9cp03802g
|View full text |Cite
|
Sign up to set email alerts
|

Topological ferroelectric nanostructures induced by mechanical strain in strontium titanate

Abstract: A new synthesis method of ferroelectric nanostructures: mechanical strain induces topological polarization in nanoporous SrTiO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Based on these data, we consider that these dislocations influence the irregular changes in birefringence and optical indicatrix presented in Figures 2-4. It was proved in articles [23][24][25][26][27][28] that the main role among the defects in STO is dislocations, which are created during crystal growth. Another factor introducing high-density dislocations in STO is crystal polishing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these data, we consider that these dislocations influence the irregular changes in birefringence and optical indicatrix presented in Figures 2-4. It was proved in articles [23][24][25][26][27][28] that the main role among the defects in STO is dislocations, which are created during crystal growth. Another factor introducing high-density dislocations in STO is crystal polishing.…”
Section: Discussionmentioning
confidence: 99%
“…This points to the huge influence of local elastic stresses on crystal properties. The rich literature, to mention a few [23][24][25][26][27][28], on the defects in STO crystal, indicates the main role of dislocations created during crystal growth and/or their polishing. This becomes clearly apparent in a thin crystal with a thickness of 30 µm.…”
Section: Birefringence and Optical Indicatrix Orientations In Srtio3 ...mentioning
confidence: 99%
“…One of the first theoretical predictions of the topological polar phase was made in the 2000s, where the polar vortex phase was predicted in the low dimensional ferroelectric system (i.e., PZT nanodisks, nanorods, and thin films) via ab initio calculations (Figure 3a). [ 101,102 ] Consequently, other theoretical studies have been reported on the vortex structure, [ 103–125 ] switching dynamics, [ 126–141 ] and properties [ 142–146 ] in various low‐dimensional ferroelectric systems. In particular, in 2006, using phase‐field simulations, J. Wang et al predicted the formation of polar vortex‐like structure in a ferroelectric nanodot (Figure 3b).…”
Section: Topological Polar Structuresmentioning
confidence: 99%